Adnan Khashoggi: His Life and Activities in the Military and Political Fields (1935-1990) - Ajmi, Dr. Rasool Shaheed; Hussein , Ass.Lec Wael Nasser (Thi Qar Arts Journal, 2024)
Adnan Khashoggi is a controversial figure in the world of arms dealing and politics, given the ambiguity surrounding his roles in both military and political fields. Many of his activities were conducted in secrecy, often within the realms of intelligence and arms companies, among other methods he used to amass his vast wealth. These factors prompted us to explore the enigmatic personality of Adnan Khashoggi and his activities in the military and political fields under the title “Adnan Khashoggi: His Life and Activities in the Military and Political Fields (1935-1990).”The study is divided into three sections:• The Birth, Upbringing, and Education of Adnan Khashoggi until 1962• The Beginnings of Adnan Khashoggi’s Activities in the Military and Political Fields (1962-1973)• The Development of Adnan Khashoggi’s Activities in Military Armament and Political Activities (1974-1990)The study relies on a variety of sources, most notably the book “Richest Man in the World: The Story of Adnan Khashoggi” by Ronald Kessler, which provided significant information for all three sections of the study. Additionally, the book “The Empire of Al-Fayed: The Secret File of Scandals from the Arms Dealers’ Embrace to the Princesses’ Bed” by Abdullah Kamal offered important insights, especially regarding Khashoggi’s birth, upbringing, and early activities in arms dealing and trade.